Determinants of non-compliance to hepatitis B vaccination among students of Kenya Medical Training College in Machakos sub county, Kenya - Silla, Winfred Nthambi; Juma, Joseph; Muitta, Esther (International Journal Of Community Medicine And Public Health, 2022)
Background: Hepatitis B virus (HBV) causes acute and chronic liver disease hepatitis B is an alarming population health concern affecting approximately 10% of the globe. In mortality ranking it is number ten global cause of death for an estimated one cases globally. Hepatitis B is the most important infectious occupational hazard which medical students and healthcare workers encounter. The magnitude of the problem can be gauged from the fact students/HCWs have the high prevalence of HBV carrier state in the population. Methods: The research examines determinants of noncompliance to Hepatitis B vaccination among students of the KMTC Machakos sub county. This research was conducted in KMTC campuses in Machakos Sub County in Kenya. Cross-sectional study design was employed in study where both quantitative and qualitative data amongst KMTC students on determinants of noncompliance to HBV vaccine by these KMTC students stratified random sampling technique was employed. A target of 384 was achieved by use of Fischer’s et al formula. Cronbach alpha coefficient was computed to find the validity and reliability. The data gathered was cleaned, organized, coded, and analysed through the use of SPSS, version 21.0 for quantitative data. Descriptive statistics. e.g., graphs, percentages, means and standard deviation while qualitative data was analysed using narratives based on themes and sub-themes. A chi square test was used to test the hypothetical statement by establishing the differences between the observed and expected outcomes on study variables. Results: Most of the students in KMTC indicated that they agree that they are confident in counselling patients about the prevention of HBV where 191 (48.5%) agreed while 74 (18.8%) strongly agreed that they can counselling patients while 70 (17.8%) were not sure that they can counselling patients while 14.0% and 1% they disagreed and strongly disagreed on the counselling patients on prevention of HBV. High number of respondents were confident in prescribing treatment for a patient with chronic hepatitis B where 155 (39.3%) agreed, while 69 (17.5%) were strongly agreed. R square of 99.6% of the data was achieved indicating that there was goodness in fit of the data used in assessment of on the relationship between the studied dependent and independent variables i.e. the attitudes towards Hepatitis B vaccination among students in KMTC. Conclusions: From the findings of the study, it is apparent that the level of awareness on HBV vaccination amongst students in KMTC in Machakos Sub County is high. Majority of the students have sufficient knowledge concerning it. It was found that needle stick injury is the most probable route of the disease transmission. Further, the respondents indicated sexual abstinence and vaccination as the preventive measures against the disease.